2014
DOI: 10.1007/s11661-014-2219-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Morphology on the Wear and Corrosion Resistance of Post-Treated Nitrided and Nitrocarburized 42CrMo4 Steel

Abstract: The surface of alloyed carbon steel was subjected to thermochemical modification by nitrocarburizing and nitriding with or without postoxidation in order to improve its mechanical properties, corrosion, and wear resistance. Treated samples were characterized by testing their basic properties (compound layer thickness, nitriding, nitrocarburizing depth, and surface hardness) according to standards. Detailed estimation of the modified metal surface was performed by additional testing: X-ray diffraction, microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…comprising of a N-enriched layer with a high nitrogen content on top of a C-enriched layer with a high carbon content 6,14 . This is explained by the presence of the ɛ-Fe 3 N and γ'-Fe 4 N phases found in the compound layer for all nitrocarburized samples treated at both temperatures 18,31,32 .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…comprising of a N-enriched layer with a high nitrogen content on top of a C-enriched layer with a high carbon content 6,14 . This is explained by the presence of the ɛ-Fe 3 N and γ'-Fe 4 N phases found in the compound layer for all nitrocarburized samples treated at both temperatures 18,31,32 .…”
Section: Resultsmentioning
confidence: 83%
“…The most desirable phase to comprise the microstructure of the compound layer is the single ɛ-Fe 2-3 N phase. However, it has been found that the compound layer formed by plasma nitrocarburizing usually consists of a heterogeneous mixture of ɛ-Fe 2-3 N and γ'-Fe 4 N phases 16,[17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with other surface treatment technologies, the surface of the UNSMed specimen is controllable. The surface morphology plays an important role in the wear and corrosion resistance [28,29]. Thus, it is necessary to search for an optimal arameter combination.…”
Section: Hardness and Residual Stress Distrubutionsmentioning
confidence: 99%
“…are not so critical for the results. However, the FIMEC technique has failed in testing materials with thin coatings or surface layers (e.g., kolsterized stainless steels [29][30][31], nitrided and nitrocarburized steels [32,33]), where the penetration depth is larger than the 100 µm thicknesses of the surface layers. Failure has also been reported in testing welding seams made through such high energy sources as laser and electron beam, where the diameter of the imprint is larger than the MZ widths [34].…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%